Is Bigger Better? Exploring Sustainable Delivery Models for Multi-Scale East African Smart Biogas Systems - Robinson, Benjamin L.; Pemba, Winfred; Ninsiima, Viola; Muhindo, Gideon; Chiumia, Admore; Clifford, Mike J.; Hewitt, Joseph; Muvule, Michel (MDPI AG, 2025)
With the deadline for the 17 United Nations Sustainable Development Goals (SDGs) on the horizon, the global community is forging a pathway through the ever-more complex global ecosystem to 2030. Whilst household-scale AD systems have seen significant attention, the community and commercial scales remain significantly under-researched. This paper aims to explore the state-of-the-art in energy access, AD and smart metering, and presents three scales of AD system delivery models which can potentially unlock meaningful pathways to energy access and the completion of SDG7. We achieve this through a two-phase qualitative methodology: first, an in-person participatory market systems development workshop in Malawi, and second, by leveraging experts’ knowledge of the Uganda and Malawian biogas sector to develop the case studies that illustrate the three scales of the AD system delivery model. Our findings analyse these delivery models, exploring the disconnection between digester size and delivery model, overcoming delivery model weaknesses through blended approaches to energy access, the role of digitalisation, and the importance of tailoring the delivery models to specific contexts. Ultimately, by drawing on real-world examples of AD system delivery models, this paper concludes by proposing a novel entire ecosystems or systems approach to biogas implementation through the blending of different scales of implementation. Publicly Available Content Database